KUALITAS PELAYANAN DASAR MASYARAKAT - Poppy Rahmadini; Meyzi Heriyanto (Jurnal Kebijakan Publik, 2013)
The purpose of this study was to analyze thequality of public services provided by the health center Bangkinang I Kampar regency. Theapproach taken by this research is a qualitative approach. The data collected is not the form ofnumbers, but the data comes from a script interviews, field notes, personal documents, notes,memos and other resumes, so that is the goal of this qualitative study was to portray the empiricalreality behind the phenomenon in depth, detailed and tutas. The results showed that in manyways the service provided does not seem to satisfy their customers. Still common complaints ofpatients every time they go to there.